2016
DOI: 10.1016/j.econmod.2016.05.027
|View full text |Cite
|
Sign up to set email alerts
|

The role of fiscal policy in Britain's Great Inflation

Abstract: a b s t r a c t a r t i c l e i n f oWe investigate whether the Fiscal Theory of the Price Level (FTPL) can explain UK inflation in the 1970s. We confront the identification problem involved by setting up the FTPL as a structural model for the episode and pitting it against an alternative Orthodox model; the models have a reduced form that is common in form but, because each model is over-identified, numerically distinct. We use indirect inference to test which model could be generating the VECM approximation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
1
0
1
Order By: Relevance
“…The articles found that fiscal and monetary authorities could stimulate economic growth without endangering price stability. Fan, Minford and Ou (2016) explored whether the Fiscal Theory of the Price Level (FTPL) could explain the UK inflation in the 1970s. The result showed that fiscal policy had a substantial role in determining inflation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The articles found that fiscal and monetary authorities could stimulate economic growth without endangering price stability. Fan, Minford and Ou (2016) explored whether the Fiscal Theory of the Price Level (FTPL) could explain the UK inflation in the 1970s. The result showed that fiscal policy had a substantial role in determining inflation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Penelitian Coutinho (2012) menyatakan bahwa inflasi yang terjadi di Negara-negara Southern Mediterranean sangat dipengaruhi oleh defisit fiskal Negara. Mendukung penelitian Coutinho (2012), penelitian yang dilakukan oleh Fan (2016) memberikan hasil bahwa kebijakan fiskal mempunyai peran besar terhadap terjadinya inflasi di Inggris. Masih dari sektor riil sebagai penyebab inflasi, penelitian Cerra (2016) memberikan hasil bahwa harga minyak dunia sebagai produksi dari penerimaan negara terbukti berpengaruh terhadap tingkat inflasi di Venezuela.…”
Section: Indonesiaunclassified